Magnesium and Phosphate Ion Levels in Mechanically Ventilated Patients Treated at Persahabatan Hospital’s Intensive Care Unit (ICU) and Respiratory Intensive Care Unit (RICU) in 2018 - Filemon Suryawan Handjaja; Menaldi Rasmin; Prasenohadi Prasenohadi; Ernita Akmal (Jurnal Respirologi Indonesia, 2023)
Background: History shows that respiratory system has a long and complicated arrangement so that many factors can affect a human’s ability to breathe. Some electrolytes often considered as most important are sodium (Na+), potassium (K+), calcium (Ca2+) and chloride (Cl-). Other than that, magnesium (Mg2+) and phosphate (PO43-) are also important in all processes, especially at the neuromuscular junction and in muscle cells as adenosine triphosphate (ATP). Some researchers have found that PO43- affected patients’ clinical condition and ventilator weaning success, although Mg2+ gave inconsistent results. Until now, there have not been any studies or data about the significance of Mg2+ and PO43- in ventilator weaning in Indonesia.Methods: This was a cross sectional study with total sampling. A vein blood sample was taken after ICU/RICU admission at Persahabatan Hospital. Blood sample was taken consecutively until it reached a minimum of 30 subjects (pilot study). All patients found with mechanical ventilation were included, except for patients with complicated procedure (e.g. avian influenza, multidrug-resistant tuberculosis). Blood sample was analyzed for Mg2+, inorganic phosphate (Pi) and other additional tests. Failure in weaning was defined as reintubation within 48 hours after extubation or failure in the spontaneous breathing trial (SBT).Results: Of the 31 subjects evaluated, there were 3 patients with weaning failure. The median Mg2+ value was 0.5 (0.5-2.6) in successfully weaned patients and 0.6 (0.6-2.7) in patients with weaning failure, lower than its normal value. The mean Pi value was 4.21±1.17 (normal value) in successfully weaned patients and 5.43±0.47 (high value) in patients with weaning failure. Further analysis found that no significant relation was found between weaning and patient’s characteristics other than heart rate and Ca2+, although it was not clear if there were some biases which could affect these results. Low Mg2+ value was observed in 23 subjects, no low Pi value was seen in all subjects, high Mg2+ value was found in 1 subject, high Pi value was observed in 11 subjects, and the rest was in the normal range.Conclusion: The median Mg2+ value in both weaning groups (successful and failed) were below the normal limit at 0.5 (0.5-2.6) and 0.6 (0.6-2.7). Mean Pi value in the successful weaning group was 4.21±1.17 (within normal range), and the value in failed weaning group was 5.43±0.47 (above normal range).